A journal of a voyage of discovery to the Arctic regions, in His Majesty's ships Hecla and Griper, in the years 1819 & 1820. - Fisher, Alexander. (London, Longman, Hurst, Rees, Orme, and Brown, 1821)
Journal of Parry's first voyage. Mode of access: Internet.